(untitled) (Research, Society and Development, 2021)
This research had for objective inquire in the articles published in the journal Química Nova na Escola (QNESC), how the theme of Chemistry teachers’ education was understood by researchers in the period 1995-2020. The results showed that the majority of articles on this field were published in the last twelve years of the period. The methodology for data collection and analysis was inspired by Discursive Textual Analysis. From the data, it was possible to highlight some trends regarding what has been disclosed in QNESC regarding the topic in question. Among them we list: Initial training; Continuing education; Teacher professionalization; Pedagogical practice; which had already been identified in previous research. However, two new categories emerged from the data, called Articles that mix categories and Other themes and teacher education. There was also a lack of articles referring to Continuing Education, which is a gap to be investigated.